(untitled) (CAHIERS MAGELLANES-NS, 2024)
Ficus bengalensis Linn.belongs to family Moraceae is considered as safe, effective and economical for various ailments in Indian traditional system of medicine viz. antidiabetic, hypocholesterolaemic and hypolipidaemic effects etc. We planned our work as to collect stem barks of mentioned plant drug from different geographical regions and extract out by 95% v/v ethanol and evaluated for antidiabetic activity. Code names for plant drugs collected from Delhi, Gujarat and Uttaranchal were given as (FB/DL), (FB/GJ) and FB/UA respectively. All of the alcoholic extracts were compared for antidiabetic activity to evaluate the effects of climatic and atmospheric conditions on chemical composition and ultimately on pharmacological actions of the plant drug. Six animal groups having six Wister albino rats in each group were made. Three groups were served as Normal Control, Diabetic Control and Reference Standard. Other three groups of rats were treated by alcoholic extracts of plant drugs at a dose of 250 mg/kg Body weight. All the animal groups were treated for seven days. All the extracts decreased blood glucose level significantly (P<0.05) when compared to control group. The effect of FB/DL was more and it reduced blood glucose level up to 28.26%. Percentage reduction in blood glucose level by FB/GJ, and FB/UA was 24.21% and 22.62% respectively. While Glibenclamide reduced glucose level up to 39.05%.